2018
DOI: 10.2174/1567205014666170704113405
|View full text |Cite
|
Sign up to set email alerts
|

Ongoing Electroencephalographic Activity Associated with Cortical Arousal in Transgenic PDAPP Mice (hAPP V717F)

Abstract: PDAPP mice were characterized by less changes in the brain arousal during an active state as revealed by frontoparietal EEG rhythms. Future studies will have to cross-validate the present results on large animal groups, clarify the neurophysiological underpinning of the effect, and test if the disease modifying drugs against AD amyloidosis normalize those candiate EEG biomarkers in PDAPP mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 0 publications
3
13
2
Order By: Relevance
“…In the present study, we reported a negative outcome, namely the lack of significant abnormalities at frontoparietal theta rhythms in the TASTPM mice in contrast to those reported in the PDAPP mice in the study by [40]. TASTPM mice have a Swedish double mutation in human APP, tangles are absent, and neural loss is relatively mild, appearing only at 10 months of age [35,36].…”
Section: Discussioncontrasting
confidence: 46%
“…In the present study, we reported a negative outcome, namely the lack of significant abnormalities at frontoparietal theta rhythms in the TASTPM mice in contrast to those reported in the PDAPP mice in the study by [40]. TASTPM mice have a Swedish double mutation in human APP, tangles are absent, and neural loss is relatively mild, appearing only at 10 months of age [35,36].…”
Section: Discussioncontrasting
confidence: 46%
“…Furthermore, increased cortical neuronal hyperactivity and excitability generating epileptiform activity may be associated with earlier clinical onset of AD and faster disease progression (Amatniek et al, 2006;Cretin et al, 2016;de Waal et al, 2011;Horvath et al, 2016Horvath et al, , 2018Vossel et al, 2016). In the same line of "overexcitation" hypothesis, transgenic mouse models of AD with APP and/or PS1 mutations showed brain amyloid plaque deposition and neurodegeneration, cognitive deficits, alterations in on-going dominant EEG oscillatory activity recorded in quiet wakefulness, and epileptiform activity (Del Percio et al, 2018;Gurevicius et al, 2013;Micotti et al, 2015;Palop et al, 2009).…”
Section: Resting State Alpha Rhythms Do Change In Smc Seniors With High Education Levelmentioning
confidence: 99%
“…On the other hand, transgenic mouse models with AD neuropathology pointed to abnormalities in ongoing EEG activity and epileptiform activity. Transgenic mice with APP and PS1 mutations inducing progressive accumulation of Abeta42 and diffuse plaques in the cerebral cortex, basal ganglia, and thalamus did manifest not only abnormalities in memory processes and ongoing cortical delta activity in the quiet wakefulness (55)(56)(57)(58), but also seizures or subclinical, non-convulsive, and epileptiform EEG activity including cortical and hippocampal spikes and sharp waves (59)(60)(61)(62).…”
Section: Discussionmentioning
confidence: 99%